Biocompatible ionized air alleviates rat osteoarthritis by modulating polarization from M1 to M2 macrophages - Haoran Yu; Chengbiao Ding; Zhongyao Hu; Qi Liu; Xuesong Gu; Junyan He; Yiqun Yan; Shenrui Yu; Lin Gao; Wendan Cheng; Zhengwei Wu; Juehua Jing (Scientific Reports)
Abstract The imbalance in the proportion of M1/M2 macrophage polarization is a crucial contributor to the persistent progression of osteoarthritis (OA). This study aimed to evaluate the effects of low-dose biocompatible ionized air (BIA) on macrophage polarization and its subsequent chondroprotective effects, thereby validating the potential of BIA in slowing the progression of OA. In vitro experiments demonstrated that BIA modulates the polarization of M1 macrophages toward the M2 phenotype via the ROS-mediated STAT6 pathway. This shift reduces the expression of pro-inflammatory mediators while increasing the expression of anti-inflammatory mediators and pro-chondrogenic factors, leading to an improved microenvironment surrounding chondrocytes. The direct benefits of this improved microenvironment include enhanced chondrocyte viability, inhibition of apoptosis, and reduced degradation of the extracellular matrix. In vivo studies in rats showed that BIA inhibited M1 macrophage infiltration in the synovium, upregulated the proportion of M2 macrophages, alleviated cartilage degeneration, and delayed OA progression. This gas-based regulatory strategy may open new avenues for the treatment of OA.